TRANSLATION STRATEGIES OF ZOONYMS IN ENGLISH AND UZBEK CHILDREN’S POETRY – LITERAL VS. CULTURAL ADAPTATION IN TRANSLATION - Numonova, Mukharramkhon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
The paper explores translation of zoonyms in English and Uzbek children poetry which are names of animals with emphasis on whether to be literal in translation or adapt the work to suit the culture. A collection of original poems in both languages was studied to assess the manner in which translators approach semantic and cultural as well as affective elements of animal references. The analysis concludes that the concept of literal translation keeps the denotative meaning intact and, in most cases, it runs the risk of losing cultural and emotional depth, whereas the adaptive approach improves the understanding, the cultural relatability, and the emotional colour of the message to the target audience. These results are relevant to the field of literary translation, cross-cultural pedagogy, and children literature instruction, as they have shown that it is essential to choose the translation strategies with preservation of both significance and emotional appeal.